Literature review: Personal hygiene genitalia and adolescent reproductive health - Sukmawati, Sukmawati; Wahjuni Utami, Jacoba Nugrahaningtyas; Astuti, Tutik (Institute of Computer Science (IOCS), 2025)
Genital hygiene is an essential aspect of maintaining adolescent reproductive health. Poor hygiene practices can increase the risk of infections and other health problems. This study aims to review the relationship between genital personal hygiene and adolescent reproductive health based on various previous studies. The method used was a literature review of eleven scientific articles that discussed genital hygiene, reproductive health education, and factors that affect adolescent behavior in maintaining personal hygiene. The sources studied include quantitative and qualitative research from various countries. The results showed that teenage knowledge about genital hygiene was closely related to hygiene behavior. Health education, the role of parents, and effective methods of conveying information have been proven to contribute to increasing adolescents' awareness of the importance of genitalia hygiene. However, the research still has limitations, such as the lack of longitudinal studies and the lack of focus on adolescent boys. The conclusions of this review confirm that proper education about genital hygiene is essential to prevent reproductive health problems. Further research is needed with a wider population coverage, a more varied approach to methods, and the use of technology in genital hygiene education for adolescents.